ANTIHYPERURICEMIA ACTIVITY OF THE ETHANOL EXTRACT OF ROSELLE CALYX AND ITS FRACTION (HIBISCUS SABDARIFFA LINN) ON MALE WISTAR RATS - Wahyuningsih, Sri; Sukandar, Elin Yulinah; ., Sukrasno; Lofika, Debby Nadya (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The objective of this study was to determine anti-hyperuricemia activity of ethanol extract of roselle calyx (Hibiscus sabdariffa L) and its fraction on male Wistar rats. Methods: Two different methods were used. First method induction was done by giving potassium oxonate and diet high purine whereas allopurinol as a comparison. The parameter was level uric acid in serum (uricostatic activity). Second methods induction was done by giving potassium oxonate intraperitoneally and sodium urate orally; with pprobenecid as comparison Parameters used were uric acid level in serum and urine (uricosuric activity). Results: Ethanol extract roselle calyx at a dose of 40 mg/kg bw, water fraction at a dose of 37.5 mg/kg bw and ethyl acetate fraction at a dose of 6.25 mg/kg bw at day 14 showed a significant reduction in serum uric acid level compared to control group (p<0.05). Besides that ethanol extract of Roselle calyx at dose 80 mg/kg bw, water fraction at doses 37.5 and 75 mg/kg bw also ethyl acetate at doses 6.25 and 12.5 mg/kg bw had uricosuric effect that increased the excretion of uric acid in urine significantly compared to control group (p<0.05). Conclusion: The water fraction of roselle calyx at doses 37.5 and 75 mg/kg bw and ethyl acetate at dose 6.25 and 12.5 mg/kg bw was effective as an anti-hyperuricemic agent. The ethanol extract of rosele calyx and its fraction had a uricosuric effect similar to probenecid. The best uricosuric effect was showed by ethyl acetate fraction at dose 6.25 mg/kg bw. Keywords: Hibiscus sabdariffa Linn, Water fraction, Ethyl acetate fraction, Calyx, Uric acid, Antihyperuricemia